2004
DOI: 10.1038/ni1131
|View full text |Cite
|
Sign up to set email alerts
|

Nod1 responds to peptidoglycan delivered by the Helicobacter pylori cag pathogenicity island

Abstract: Epithelial cells can respond to conserved bacterial products that are internalized after either bacterial invasion or liposome treatment of cells. We report here that the noninvasive Gram-negative pathogen Helicobacter pylori was recognized by epithelial cells via Nod1, an intracellular pathogen-recognition molecule with specificity for Gram-negative peptidoglycan. Nod1 detection of H. pylori depended on the delivery of peptidoglycan to host cells by a bacterial type IV secretion system, encoded by the H. pylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
1,136
9
17

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,098 publications
(1,197 citation statements)
references
References 47 publications
35
1,136
9
17
Order By: Relevance
“…Signals that recruit neutrophils and activated macrophages contribute to the killing of microbes, but more importantly, they also lead to activation of adaptive immune responses. In the case of H. pylori infection, it is generally accepted that TLRs, in addition to other receptors such as Nod1 (Viala et al, 2004), are at least partly involved in the initial recognition of the bacterium. However, there has been much debate about whether H. pylori's LPS is recognized by TLR4 or TLR2 (whose natural ligands include peptidoglycan, lipopeptides and lipoteichoic acid from gram-positive bacteria).…”
Section: H Pylori-induced Gastric Cancer Modelmentioning
confidence: 99%
“…Signals that recruit neutrophils and activated macrophages contribute to the killing of microbes, but more importantly, they also lead to activation of adaptive immune responses. In the case of H. pylori infection, it is generally accepted that TLRs, in addition to other receptors such as Nod1 (Viala et al, 2004), are at least partly involved in the initial recognition of the bacterium. However, there has been much debate about whether H. pylori's LPS is recognized by TLR4 or TLR2 (whose natural ligands include peptidoglycan, lipopeptides and lipoteichoic acid from gram-positive bacteria).…”
Section: H Pylori-induced Gastric Cancer Modelmentioning
confidence: 99%
“…Nod1 is involved in host defense towards intracellular pathogens including Shigella flexneri, 56 enteroinvasive E. coli, 57 Pseudomonas aeruginosa, 58 Chlamydiae pneumoniae, 59 as well as non invasive H. pylori which delivers muropeptides within the epithelial cells though its type IV secretion apparatus encoded by the cag pathogenicity island. 60 Nod2 is involved in the sensing of Streptococcus pneumoniae 61 and Mycobacteria. 62 In vivo studies in mice have shown an important role for Nod2 in bacterial clearance since an increased bacterial load was observed in the liver and spleen of Nod2-deficient mice compared to control mice after oral challenge with L. monocytogenes.…”
Section: Nods and Pg Motifsmentioning
confidence: 99%
“…Its genome contains a cagpathogenicity island (cagPAI), encoding proteins for a specialized type IV secretion system (T4SS), which injects virulence factors directly into the host cytoplasm of infected epithelial cells. So far, peptidoglycans (Viala et al, 2004) and the CagA protein (Asahi et al, 2000;Backert et al, 2000;Odenbreit et al, 2000;Stein et al, 2000) are known to translocate into the infected epithelial host cell. Translocated CagA induces cellular processes, which lead to stimulation of cell dissemination followed by cell motility, and invasive growth in gastric epithelial cells (Segal et al, 1999;Bagnoli et al, 2005).…”
Section: Introductionmentioning
confidence: 99%